1973
DOI: 10.1136/hrt.35.8.849
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular haemolysis and thrombocytopenia in left ventricular outflow obstruction.

Abstract: Twenty-four patients with various types of isolated discrete aortic stenosis of a wide range of severity or with muscular obstruction to left ventricular outflow were studied haematologically and by cardiac catheterization and angiocardiography. Patients had haematocrits, reticulocyte, platelet, and megathrombocyte counts, serum haptoglobin, and lactic dehydrogenase performed; urine specimens were examined for haemosiderin and peripheral blood smears examinedfor schistocytes. Seventeen patients had 51chromium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 12 publications
0
24
0
3
Order By: Relevance
“…When a pressure gradient of more than 50 mmHg is present across a valve, shearing stress can exceed 4,000 dynes/cm 2 . Theoretically, a shearing stress of more than 3,000 dynes/cm 2 can cause fragmentation of red blood cells (2)(3)(4). The present patient's pressure gradient was more than 150 mmHg, which was potentially high enough to cause hemolysis.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…When a pressure gradient of more than 50 mmHg is present across a valve, shearing stress can exceed 4,000 dynes/cm 2 . Theoretically, a shearing stress of more than 3,000 dynes/cm 2 can cause fragmentation of red blood cells (2)(3)(4). The present patient's pressure gradient was more than 150 mmHg, which was potentially high enough to cause hemolysis.…”
Section: Discussionmentioning
confidence: 62%
“…Intravascular hemolysis may occur with hemolysis-prone erythrocytes or, if shear forces are great enough, with normal erythrocytes (1). Jacobson et al (2) reported that intravascular hemolysis develops when pressure gradients of 50 mmHg or more occurred in aortic stenosis. When a pressure gradient of more than 50 mmHg is present across a valve, shearing stress can exceed 4,000 dynes/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Intracardiac high velocity jets through stenosed or incompetent orifices can cause intravascular hemolysis, but few case reports have evaluated intravascular hemolysis in patients with native valvular heart disease. 11,12) Accordingly, we evaluated the presence of intravascular hemolysis by measuring erythrocyte creatine and examined the relation between erythrocyte creatine and hemodynamic parameters in patients with aortic stenosis.…”
Section: Ntravascular Hemolysis Has Been Identified In Patients Withmentioning
confidence: 99%
“…The enhanced shear stress associated with stenosis of the native aortic valve can theoretically induce intravascular hemolysis. [31][32][33] Aortic stenosis is sometimes associated with loss of high molecular von Willebrand multimers and with a greater tendency to bleed. 34,35 Although these issues are of clinical significance only in cases of severe anemia requiring transfusion, mild anemia in our subjects may exist in part because of these mechanisms.…”
Section: Prognostic Factors For Progression Of Early-stage Cavdmentioning
confidence: 99%